The Complementary Value of Magnetic Resonance Imaging and Vibration-Controlled Transient Elastography for Risk Stratification in Primary Sclerosing Cholangitis. (December 2019) - Cazzagon, Nora; Lemoinne, Sara; El Mouhadi, Sanaâ; Trivedi, Palak J.; Gaouar, Farid; Kemgang, Astrid; Ben Belkacem, Karima; Floreani, Annarosa; Hirschfield, Gideon; Chretien, Yves; Housset, Chantal; Motta, Raffaella; et al.
Abstract : OBJECTIVES: Magnetic resonance (MR) risk scores and liver stiffness (LS) have individually been shown to predict clinical outcomes in primary sclerosing cholangitis (PSC). The aim of this study was to assess their complementary prognostic value. METHODS: Patients with PSC from 3 European centers with a 3-dimensional MR cholangiography available for central reviewing and a valid LS measurement assessed by vibration-controlled transient elastography by FibroScan performed within a 6-month interval were included in a longitudinal retrospective study. The MR score (Anali) without gadolinium (Gd) was calculated according to the formula: (1 × dilatation of intrahepatic bile ducts) + (2 × dysmorphy) + (1 × portal hypertension). The primary end point was survival without liver transplantation or cirrhosis decompensation. The prognostic values of LS and Anali score without Gd were assessed using Cox proportional hazard models. RESULTS: One hundred sixty-two patients were included. Over a total follow-up of 753 patient-years, 40 patients experienced an adverse outcome (4 liver transplantations, 6 liver-related deaths, and 30 cirrhosis decompensations). LS and Anali score without Gd were significantly correlated (ρ = 0.51, P < 0.001) and were independently associated with the occurrence of an adverse outcome. Optimal prognostic thresholds were 10.5 kPa for LS and 2 for the Anali score without Gd. Hazard ratios (95% confidence interval) were 2.07 (1.06–4.06) and 3.78 (1.67–8.59), respectively. The use in combination of these 2 thresholds allowed us to separate patients into low-, medium-, and high-risk groups for developing adverse outcomes. The 5-year cumulative rates of adverse outcome in these 3 groups were 8%, 16%, and 38% ( P < 0.001), respectively. DISCUSSION: The combined use of MRI and vibration-controlled transient elastography permits easy risk stratification of patients with PSC.